How to protect oneself against medical errors - F. F. Tetenev (Бюллетень сибирской медицины)
The paper is devoted to the problem of medical errors in diagnosing. With the Siberian clinical school taken as an example, the theory of formation of clinical experience from the gradual accumulation of experience by the school founders to the active formation of clinical thinking through the use of the theory of diagnosing is presented.